Does individual quality mask the detection of performance trade-offs? A test using analyses of human physical performance - Wilson, R. S.; Niehaus, A. C.; David, G.; Hunter, A.; Smith, M. (The Journal of Experimental Biology, 2014)
Why are performance trade-offs so rarely detected in animals when their underlying physiological basis seems so intuitive? One possibility is that individual variation in health, fitness, nutrition, development or genetics, or `individual quality`, makes some individuals better or worse performers across all motor tasks. If this is the case, then correcting for individual quality should reveal functional trade-offs that might otherwise be overlooked. We tested this idea by exploring trade-offs in maximum physical performance and motor skill function in semi-professional soccer players. We assessed individual performance across five maximum `athletic` tasks providing independent measures of power, stamina and speed, as well as five soccer-specific `motor skill` tasks providing independent measures of foot control. We expected to find functional trade-offs between pairs of traits (e.g. endurance versus power/speed tasks or specialist-generalist performance) - but only after correcting for individual quality. Analyses of standardised raw data found positive associations among several pairs of traits, but no evidence of performance trade-offs. Indeed, peak performance across a single athletic task (degree of specialisation) was positively associated with performance averaged across all other athletic tasks (generalist). However, after accounting for an individual's overall quality, several functional trade-offs became evident. Within our quality-corrected data, 1500 m-speed (endurance) was negatively associated with squat time (power), jump distance (power) and agility speed - reflecting the expected speed-endurance trade-off; and degree of specialisation was negatively associated with average performance across tasks. Taken together, our data support the idea that individual variation in general quality can mask the detection of performance trade-offs at the whole-animal level. These results highlight the possibility that studies may spuriously conclude certain functional trade-offs are unimportant or non-existent when analyses that account for variation in general quality may reveal their cryptic presence.